(untitled) (Fiep Bulletin - online, 2014)
The purpose of this article was to identify the factors that influence the rate of adherence in individuals in the practice of a bodybuilding gym in the neighborhood Anita Garibaldi, Joinville, SC. To identify the factors that influence adherence to bodybuilding exercises in subjects older than 18 years with more than 6 months of practice questionnaire was used for research on adherence to physical exercise in gym Morales (2002) and was completed by the individual own gym (at the beginning or end of the training of the practitioner). The questionnaire included personal and demographic information, aspects of lifestyle, environmental factors and behavioral factors. The sample of the academy was determined randomly. We used the program Excel for Windows for tabulation and plotting of data and SPSS 16.0 for descriptive statistics and correlacional data. The results obtained are 110 bodybuilders, and (69 men and 41 women). The first main factor to remain in the exercise program cited by practitioners is: health (40.9%), results (20.9%) and aesthetics (12.7%). The second main factors to remain in a program of exercise according to practitioners are: pleasure (28.2%), results (20.9%) and health (14.5%). For the first main factor favoring the withdrawal of the practitioner was quoted demotivation (28.2%), time (26.4%) and disease (20.9%). The second main factor that would favor the withdrawal time (48.2%), motivation (14.5%) and disease (10%). Data obtained show that practicing bodybuilding stopped aim only for aesthetic purposes and gain strength, but are directed at gaining and maintaining health.